Cinema Owners Association Biografia a.s. in Prague (1919/1920-1930) - Lachman, Tomáš (Iluminace, 2008)
History of Biografia a.s. in Prague in 1919-1930, its establishment and business characteristics.
Keywords: companies; interwar era; film distributors; film history; archive funds